Patterns in the history of the commentation on the so-called ḥadīth Ibn Masʿūd - Eich, Thomas (Journal of Arabic and Islamic Studies, 2019)
This paper analyzes the so-called Ibn Masʿūd ḥadīth (see below) on two levels: the specific wording of the ḥadīth on the one hand and a significant portion of the commentation written about it since the 10th century until today on the other. This aims at three things. First, I will show how the ḥadīth’s exact wording still developed after the stabilization of the material in collections. Although this development occurred only on the level of single words, it can be shown that it is a reflection of discussions documented in the commentaries. Therefore, these specific examples show that there was not always a clear line separating between ḥadīth text and commentaries on that text. Second, the diachronic analysis of the commentaries will provide material for a nuanced assessment in how far major icons of commentation such as Nawawī and Ibn Ḥajar al-ʿAsqalānī significantly influenced following generations in composing their respective commentaries. Third, I will argue that in the specific case study provided here significant changes in the commentation can be witnessed since the second half of the 19th century which are caused by the spread of basic common medical knowledge in that period.